Improvement of Emulsion Stability and Plugging Performance of Nanopores Using Modified Polystyrene Nanoparticles in Invert Emulsion Drilling Fluids - Huang, Xianbin; Meng, Xu; Wu, Leping; Gao, Chongyang; Lv, Kaihe; Sun, Baolu (Frontiers in Chemistry, 2022)
Drilling fluid invasion and pressure transmission caused by the development of micropores and fractures in shale oil and gas formations are the major factors contributing to wellbore instability during drilling using oil-based drilling fluids (OBFs). In this study, a modified polystyrene latex (MPL) material was synthesized through emulsion polymerization and was characterized using Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), particle size analysis, scanning electron microscopy (SEM) observations, and contact angle testing. The influence of the MPL on the stability of a water-in-oil emulsion was analyzed via sedimentation observations and electrical stability tests. The effects of the MPL on the plugging mechanism of white oil and water-in-oil emulsions were evaluated using 0.1 μm to 1.0 μm micro-porous filtration films. The experimental results revealed that the MPL has a favorable thermal stability, with an initial thermal decomposition temperature of 363°C, a median particle size (D50) of 233 nm, and a three-phase contact angle of 103.5°. The MPL can enhance the sedimentation stability of an emulsion to a considerable extent and can improve the electrical stability (ES) of the emulsion, which is conducive to the stability of OBFs. Due to the deformability of the MPL, it has a wide range of adaptations for micro-scale pores and fractures. In both the white oil and water-in-oil emulsions, the MPL can reduce the filtration loss through microporous membranes with pore sizes of 0.1–1.0 μm to within 10 mL. This paper details the methodology of the synthesis of nanomaterials that can effectively plug a formation’s nanopores and fractures; thereby, stabilizing OBFs.